2016
DOI: 10.1186/s12864-016-3131-2
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the molecular basis of oxidative stress management in a drought tolerant rice genotype Nagina 22

Abstract: BackgroundDrought stress tolerance for crop improvement is an important goal worldwide. Drought is a complex trait, and it is vital to understand the complex physiological, biochemical, and molecular mechanisms of drought tolerance to tackle it effectively. Osmotic adjustment, oxidative stress management (OSM), and cell membrane stability (CMS) are major components of cellular tolerance under drought stress. In the current study, we explored the molecular basis of OSM in the drought tolerant rice variety, Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…'IR64' has the lowest root to shoot ratio, almost 1/3 of that in 'Putih Cempaka'. 'IR64' has been known as drought sensitive rice cultivar (Prakash et al, 2016). The high root to shoot ratio is to increase water uptake (Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…'IR64' has the lowest root to shoot ratio, almost 1/3 of that in 'Putih Cempaka'. 'IR64' has been known as drought sensitive rice cultivar (Prakash et al, 2016). The high root to shoot ratio is to increase water uptake (Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide analysis of genes of GR in rice has shed light on evolutionary conserved domains, which helps in better understanding of its role under normal and stressed conditions (Trivedi et al 2013). Genome-wide SNP analysis of antioxidative genes in rice has revealed functional polymorphism between resistant and susceptible genotypes that can be used to identify superior alleles in rice population studies (Prakash et al 2016). Integration of conventional plant breeding methods, together with advanced genomic tools and phenotyping methods, will rapidly deliver superior breeding material with improved genetic gains.…”
Section: Molecular Breedingmentioning
confidence: 99%
“…Although, complex traits such as yield are routinely dissected into their component traits namely grain size, test weight and number of productive tillers per plant in rice, sometimes resulting in the development of functional markers, the same is not true in drought stress research (Prakash et al, 2016). Earlier molecular genetic analyses identified several QTLs of secondary traits important to drought tolerance such as root architecture, leaf water status, panicle water potential, osmotic adjustment and relative water content.…”
Section: Detection Of Quantitative Trait Loci (Qtls) For Useful Drougmentioning
confidence: 99%
“…Recently, 6 QTLs for RDR were identified using 1 019 883 single-nucleotide polymorphisms (SNPs) (Lou et al, 2015). Prince et al (2015) identified two QTLs for canopy temperature, 1 QTL for leaf drying and 1 for SPAD under managed stress and in a rainfed target drought stress environment, respectively. The introduction of traits that contribute to drought avoidance or tolerance should improve resistance of rice to drought and this strategy therefore has considerable potential to increase rice production in areas prone to drought (Fukai and Cooper, 1995;Nguyen et al, 1997).…”
Section: Genes/qtl Underlying Drought Secondary Traitsmentioning
confidence: 99%